2012
DOI: 10.1590/s1517-86922012000500007
|View full text |Cite
|
Sign up to set email alerts
|

Análise do controle do equilíbrio em surfistas durante a postura ereta

Abstract: Background: Surfing is a sport that has become considerably popular, which increased interest in research about the aspects that can influence on the performance of these athletes, such as injuries, aerobic fitness and reaction time. Due to the ever-changing environment and high instability required for surfing, the surfers must develop some neuromuscular skills (agility, balance, muscle strength and flexibility) to acquire better performance in this modality. Nevertheless, there are still few scientific studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This nding is more controversial at the current time, other researchers have compared the static balance of surfers, Chapman et al (2008) assessed the static balance of elite and intermediate surfers on a balancing platform and found no difference between the two groups. Furthermore, Alcantara et al (2012) found no differences in static balance performance between recreational surfers and controls. However, as sur ng takes place in an ever-changing and volatile environment, static equilibrium enhancements and needs may not be very clearly discernable (Hrysomallis, 2011).…”
Section: Analysis Of Changes In Static Balancementioning
confidence: 75%
See 1 more Smart Citation
“…This nding is more controversial at the current time, other researchers have compared the static balance of surfers, Chapman et al (2008) assessed the static balance of elite and intermediate surfers on a balancing platform and found no difference between the two groups. Furthermore, Alcantara et al (2012) found no differences in static balance performance between recreational surfers and controls. However, as sur ng takes place in an ever-changing and volatile environment, static equilibrium enhancements and needs may not be very clearly discernable (Hrysomallis, 2011).…”
Section: Analysis Of Changes In Static Balancementioning
confidence: 75%
“…Due to the ever-changing environments and high level of instability required for sur ng, surfers must develop a number of neuromuscular skills (agility, balance, muscle strength and exibility) for better performance. This involves visual deprivation (eyes opening or closing) and impairment of somatic sensation (stabilizing surfaces or using bubbles) (Alcantara et al, 2012). The training methods in this study created an unstable environment, trained somatosensory perception, and enhanced dynamic balance.…”
Section: Analysis Of Changes In Dynamic Balancementioning
confidence: 99%
“…Similarly, recreational surfing may cause beneficial adaptations to the neuromuscular function on the long term, with lower rates of posture oscillation in the standing position, with closed eyes and in a smooth surface 2 . However, when we compare amateur surfers with active individuals who perform different sports, there is no different in their balance control 10 . Thus, we conclude that lower back pain in surfers is not caused by posture instability, since higher rates of oscillation may be related to low back pain 11 .…”
Section: Introductionmentioning
confidence: 96%